The Emerging Roles of Information Management in Government Agencies - Filzah Mohamad Saodi, Norsyafiqah; Sharis Ikhwan Idris, Muhammad; Aiza Saharuddin, Noradilah; Farik Mat Yatin, Saiful; Hussin, Norhayati; Ab Rahman, Azmi (International Journal of Engineering and Technology, 2018)
Public ICT Strategic Plan or knowingly known as “Pelan Strategik ICT Sektor Awam (PSICTSA) 2016-2020 has been created to uphold the successful implementation of National Transformation Programme with regards of increasing system delivery among public agency as well as produce high-impact services and conducive ambience, eventually resulting to effective and efficient ICT delivery system. In short, the government has put a huge effort to ensure this ICT Strategic Plan will aid public sector to keeping up with sophisticated system at the same time improve the reputation of public delivery system within the government agency. Hence, government has highlight several guidelines for the implementation of PSICTSA, a set of elements that uphold the Government mission in striving Vision 2020 in line with the full leverage of information technology. As a result, well-developed and comprehensive strategic plan within public sector reflect high generate business total income and consistent revenue through ICT exploitation. Eventually, all these conveniences will assist the public sector’s staffs to work in high resourceful manner at the same time brings thousands of benefits towards them in performing the daily tasks. Therefore, the purpose of this paper is to highlights the strategy of transforming the ICT division to Information Management Division within Public sector either ministry level or government agencies in Malaysia. An oral interview session has been conducted in one of the government agencies to collect and gather supportive information. The study shows that Public ICT strategic plan is essential component which reflects a clear visions for organization’s future and established a set of goals advocate to improve organization as well achieve a quality shared vision. Ideally, the result drives the organizational to become a high-competitive company and improving the performance of overall personnel.